JNK Signaling Pathway Suppresses LPS-Mediated Apoptosis of HK-2 Cells by Upregulating NGAL. (24th April 2020) - Han, Mei; Pan, Yuxia; Gao, Mengying; Zhang, Junli; Wang, Fan
Abstract : Objective . To explore the role of the c-Jun N-terminal kinase (JNK) signaling pathway in upregulated NGAL expression and its antiapoptotic mechanism in lipopolysaccharide (LPS)-mediated renal tubular epithelial cell injury. Methods . In vitro, HK-2 cells were divided into five groups (Con, LPS 1 h, LPS 3 h, LPS 6 h, and LPS 12 h groups) based on the time of LPS (10 μ M) treatment. NGAL and caspase-3 gene expression levels were detected by RT-PCR to assess dynamic changes. HK-2 cells were pretreated with SP600125 (20 μ M) for 2 hours, followed by LPS (10 μ M) stimulation for 3 hours. NGAL and caspase-3 gene expression levels were then determined. Results . NGAL mRNA was increased significantly within 6 hours, and caspase-3 mRNA was increased within 3 hours after treatment (P < 0.05 ). Correlation analysis showed a high correlation between their expression ( r = 0.448, P < 0.05 ). After pretreatment with SP600125, mRNA expression of NGAL in the LPS group was inhibited, while that of caspase-3 was increased significantly. The NGAL mRNA expression level in the SB + LPS group was decreased significantly compared with that in the LPS group, but it was slightly higher than that in the SP group (∼1.5 times of that in the Con group). However, caspase-3 mRNA expression was increased significantly in the SB + LPS group (P < 0.001 ) (3.5 times of that in the Con group). It also showed a significant increase compared with SP and LPS groups (P < 0.001 vs. SB group; P < 0.05 vs. LPS group). We also found that NGAL and caspase 3 proteins were increased significantly in LPS and SP + LPS groups, but SP600125 decreased the NGAL level by almost 35% and increased the caspase 3 level by 50% in the SP + LPS group compared with the LPS group (P < 0.05 ). Conclusions . The JNK signaling pathway inhibits LPS-mediated apoptosis of renal tubular epithelial cells by upregulating NGAL.